Who benefits from the sanitized language of violence? - Fyjis-Walker, Matthew (International studies on military ethics,, 2024)
"Language is not neutral; it determines, and is determined, by perspective. This volume explores the role of an influential vocabulary of war, sanitised language, the language that seeks to clean up the appearance of events through euphemism, abstract words and opaque phrases. Critical discourse analysis of the language of recent military campaigns shows that the public authorities do not explain events as clearly as they might. Despite social, political and strategic incentives to use sanitised language, its use appears to undermine the democratic process and reduce public authorities' freedoms, possibly emboldening adversaries and turning away potential partners"--